2015
DOI: 10.1080/10967494.2015.1027800
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Red Tape on Citizen Satisfaction: An Experimental Study

Abstract: Red tape is one of the most often-mentioned nuisances citizens experience with government. However, there is a dearth of red tape research focusing on citizens. Therefore, the primary goal of this article is to analyze the effect of red tape on citizen satisfaction. The secondary goal is to go beyond testing a linear relationship between red tape and citizen satisfaction by examining individual factors that may moderate this relationship. In order to analyze the red tape=satisfaction relationship, we have desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 58 publications
1
70
1
Order By: Relevance
“…Using a student sample in the context of a vignette study is in line with the approach taken by, among others, Kaufmann and Feeney (2014), Tummers et al (2016) and Moynihan (2013). While the random assignment of participants ensures that meaningful conclusions can be drawn from a student sample, student samples have also been challenged as being insufficiently representative of 'real' employees.…”
Section: Methodsmentioning
confidence: 90%
“…Using a student sample in the context of a vignette study is in line with the approach taken by, among others, Kaufmann and Feeney (2014), Tummers et al (2016) and Moynihan (2013). While the random assignment of participants ensures that meaningful conclusions can be drawn from a student sample, student samples have also been challenged as being insufficiently representative of 'real' employees.…”
Section: Methodsmentioning
confidence: 90%
“…Participants in group 3 ( burden red tape ) were asked to complete a two‐page form for the agency. Similar to Tummers et al's () experiment, the document collected information that was (1) redundant to the demographic control variables already gathered during the initial survey (e.g., age, gender, study level), (2) seemingly unrelated to the document's purpose of allowance approval (e.g., the number of surveys participated so far), and (3) had excessive detail (e.g., inquiring about the quantity of telephone, online, paper‐based, face‐to‐face surveys). The document also included design elements adapted from our universities' reimbursement forms (e.g., a section to be filled out by the administration with the organization unit, cost center number, and project number).…”
Section: Methods and Datamentioning
confidence: 99%
“…Research into bureaucratic red tape has expanded our knowledge on a variety of topics, including organizational effectiveness (e.g., Pandey, Coursey, and Moynihan ), public and private sector specifics (e.g., Pandey and Kingsley ), managerial alienation (e.g., DeHart‐Davis and Pandey ), personnel recruitment (e.g., Linos and Riesch ), and career intentions (e.g., Hattke, Vogel, and Znanewitz ). The few investigations into the consequences of red tape in citizen‐state interactions (e.g., Christensen et al ; Moynihan and Herd ; Scott and Pandey ; Tummers et al ) have demonstrated that it delays the delivery of services (Bozeman, Reed, and Scott ) and imposes administrative burdens on citizens (Herd et al ). Still, there is an ongoing debate about what red tape actually is and how best to assess it.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Borry () carries this metaphor further to call formalization an organization's skeleton, which then can become diseased by red tape. In this light, scholars have looked at associations between red tape and such concepts as organizational effectiveness (Pandey, Coursey, and Moynihan ), risk‐taking behavior (Bozeman and Kingsley ), satisfaction (Giauque et al ; Tummers et al ; Kaufmann and Tummers ), and public service motivation (Moynihan and Pandey ).…”
Section: Toward a More General Perspective On Organization Structure mentioning
confidence: 99%